Cesta za otcem - Tuka, Josef (Czech Republic, 2010)
A story of Eva Langrová whose father was unjustly sentenced in communist show trials. Over the years her father spent in Jáchymov forced labor camp the distance between Eva and her father grew. The story is built around Eva’s memories of visits to her father in Jáchymov labor camp Eva and her relatives used to make once a year. After 50 years Eva sets again on a journey across Czech Republic, from Ostrava to Jáchymov, and reflects on her relationship with her father, and the past era, she grew up in. Her memories are interlarded with extracts from letters her father used to send her from prison.
Verzio Film Festival Submission
Keywords: Documentary films